Building functional warm-up routines in basketball: a narrative review of literature - Adriano Vretaros (Turkish Journal of Kinesiology, 2023)
Warming up is a crucial preparatory activity used in training sessions and games. Therefore, the aim of this investigation is to examine the construction of functional basketball warm-up routines through a narrative literature review. Four electronic databases were consulted (MEDLINE, Google Scholar, Scielo and LILACS), where 47 articles were selected that discussed warm-up routines in basketball and team sports, as well as 09 textbooks in the field of sports training and physiology of the exercise. A well-designed warm-up promotes optimization in performance and prevents the appearance of injuries. However, there are multiple choices for building warm-up routines. Thus, the structuring of a warm-up should take into account the basic methodological aspects for them to be effective, such as: duration, intensity, adopted exercises, sequence of tasks, use of additional equipment, number of routines and recovery interval. Also, in basketball, the critical times to implement warm-ups are training sessions, game days, in-game re-warm-up, and half-time re-warm-up. Each of these points requires a distinct didactic-pedagogical approach in warm-up procedures. In this way, with the acquisition of a broader view of each component involved in this process, it becomes feasible to solve these issues. Finally, it is imperative that basketball physical trainers are able to masterfully solve the practical problems of warm-up, for more assertive decision-making in relation to routines that incorporate superior results in performance and reduction of injuries.